Investigation of Wrinkling Initiation in Shear Spinning - Li Zhikun; Long Hui (MATEC Web of Conferences)
Metal spinning is a flexible and net-shape sheet forming process however its process development still heavily relies on empirical knowledge to determine process parameters to avoid processing failures, such as wrinkling. This paper develops dynamic finite element modelling of a shear spinning process to investigate wrinkling initiation and critical strains leading to wrinkling. Two processing parameters, mandrel rotational speed and roller feed rate, in spinning aluminium sheet material AA5251-H22 are investigated to ascertain the effect of the roller feed ratio on wrinkling, validated by a spinning experiment. The evolution of the maximum circumferential and radial strains on the top surface of wrinkling waves is evaluated and it has been found that they accumulate progressively with the formation of wrinkling. The wrinkling initiates when the maximum circumferential strain of the top surface of winkling waves cyclically increases and remains tensile. The FE results indicate that the dynamic effect due to a higher mandrel speed, thus a greater strain rate, is independent of the wrinkling initiation providing that the roller feed ratio remains unchanged and below a certain limit. The wrinkling initiation is the result of the circumferential strain accumulation when the roller feed ratio applied to the sheet exceeds a limit.